Self-recoverable element failure correction in circular antenna array using artificial rabbit optimization for space applications - Singh, Harbinder; Kumar, Sunil; Bhattu, Monika; Pal, Amrindra; Al Gburi, Ahmed Jamal Abdullah (Emerald Publishing, 2025)
Purpose – Phased array antennas utilized for different space applications, such as deep space vehicles, satellite communication, telemetry tracking and control communication systems, may suffer from single or multiple element failure because of the harsh space environment or long period operation of amplifiers present in them.